Socialization Of Preparation Of Financial Reports In Kesesi Village IPNU & IPPNU Organizations - Santi Nailul Izaty; Fatma Azzahra Puspita Sari; Arga Dwi Titandy; Hendri Hermawan Adinugraha; Ria Anisatus Sholihah (Peneliti Teknologi Teknik Indonesia, 2023)
Accounting knowledge is often considered difficult for many people. Many are unable to apply it. Because the practice is complicated and confusing. The benefits of this service are expected to increase understanding of basic accounting and preparation of financial reports for the IPNU & IPPNU organizations in Kesesi village. The urgency of this training is because the implementation of basic accounting and the preparation of financial reports in the IPPNU organization is still said to be not in accordance with the basic accounting standards. The service method is in the form of delivering material related to accounting and regarding how to prepare financial reports according to accounting standards. The material provided can provide insight and knowledge in the field of accounting. Through this activity it is hoped that in the future the IPNU & IPPNU organization of Kesesi village will be even better in terms of compiling financial reports, this activity will provide motivation to participants and benefit the importance of accounting in the IPNU & IPPNU organizations they participate in and with this socialization they will be helped so that they hope for activities like This may be held again in the coming year.